808. Perinatal Depression Among HIV- and TB-Infected and Uninfected Women in an Urban Slum in India: Prevalence and Associated Birth Outcomes. (26th November 2018) - Grossman, Tracy; Mathad, Jyoti S
Abstract: Background: In low- and middle-income countries, depression during pregnancy is three times more common than in the United States and is more common than postpartum depression. There have been few studies on the prevalence of antepartum and postpartum depression in India. The objective of this study was to describe the prevalence of antepartum and postpartum depression among HIV-infected and uninfected pregnant women in an urban slum in India, and to evaluate associated pregnancy and birth outcomes. Methods: This study was a longitudinal cohort study of HIV-infected and HIV-uninfected pregnant women at Sassoon General Hospital in Pune, India. Enrolled women answer questions about sociodemographics and medical history, including obstetric history. The PHQ-9 depression scale is administered during pregnancy and at 6 months postpartum. Results: Of the 189 pregnant women enrolled, 113 (60 %) exhibited at least one symptom of depression on the PHQ-9 scale with 23 (12%) women having moderate or severe depression. However, significantly fewer postpartum women had evidence of depression (60% antepartum vs. 26% postpartum, P < 0.001). Of the 77 women who had a postpartum visit, 20 (26%) also had symptoms of depression prior to delivery, but only 2 (10%) had more severe depression scores while 18 (90%) had improved scores. Thirty (39%) women with antepartum depression had resolution of symptoms postpartum and no women developed incident depression in the postpartum period. There was a trend toward increased rates of antenatal depression among HIV-infected vs. uninfected women (69% vs. 57%, P = 0.13). Both depressed and nondepressed pregnant women experienced low rates of intrauterine fetal demise, intrapartum hypertension, and preterm delivery. However, women with depression had 3-fold higher incidence of intrauterine growth restriction on prenatal ultrasound (4.4% vs. 1.5%). Conclusion: We found that the majority of pregnant women in our population experience some form of depression during pregnancy. Most women with antepartum depression experienced improvement in their mood postpartum, which contrasts with patterns of perinatal depression in developed countries. We are planning qualitative studies to understand the social contributors for antepartum depression in India, and to identify potential solutions. Disclosures: All authors: No reported disclosures.